Peranan Media Visual Terhadap Peningkatan Kosakata Siswa SD kelas 1 di SDN Wonorejo 3 Surabaya - Archielian Satrio Putro Pambudi; Anastasya Benny Pratama; Nensy Megawati Simanjuntak (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to evaluate the effectiveness of using visual media, specifically flashcards, in enhancing the vocabulary of first-grade students at SDN Wonorejo 3 Surabaya. This topic was chosen due to the importance of vocabulary development in language learning and the need for innovative teaching methods. The research method involved a quantitative approach with a pre-experimental design, collecting data through pretests and posttests on 30 students. The results showed a significant increase in students' vocabulary scores after using flashcards, with the average pretest score of 59.87 rising to 84.47 in the posttest. These findings confirm that flashcards are an effective learning medium for improving students' vocabulary. The conclusion of this study is that the use of visual media like flashcards can significantly enhance vocabulary comprehension, supporting the development of students' communication skills.